2023
DOI: 10.1111/ijsa.12417
|View full text |Cite
|
Sign up to set email alerts
|

</Click to begin your digital interview>: Applicants' experiences with discrimination explain their reactions to algorithms in personnel selection

Abstract: Algorithms might prevent prejudices and increase objectivity in personnel selection decisions, but they have also been accused of being biased. We question whether algorithm-based decision-making or providing justifying information about the decision-maker (here: to prevent biases and prejudices and to make more objective decisions) helps organizations to attract a diverse workforce. In two experimental studies in which participants go through a digital interview, we find support for the overall negative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…However, at the same time, there is also evidence that people seem to be concerned with unfair discrimination that is hard to control with algorithmic decisions (Mirowska & Mesnet, 2022). Combining those two issues, Koch‐Bayram et al (2023) recently showed that applicants who had experienced prior (human‐based) discrimination tend to view algorithmic decisions more positively than applicants without such experiences. Overall, there is still much to learn about what are the conditions for fostering the potential and for controlling the risks associated with algorithmic decision‐making, especially with respect to (perceived) fairness and diversity.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…However, at the same time, there is also evidence that people seem to be concerned with unfair discrimination that is hard to control with algorithmic decisions (Mirowska & Mesnet, 2022). Combining those two issues, Koch‐Bayram et al (2023) recently showed that applicants who had experienced prior (human‐based) discrimination tend to view algorithmic decisions more positively than applicants without such experiences. Overall, there is still much to learn about what are the conditions for fostering the potential and for controlling the risks associated with algorithmic decision‐making, especially with respect to (perceived) fairness and diversity.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…Hiring algorithms could also benefit by increasing the perceived equity of the hiring process. For example, (1) women prefer to be judged by an algorithm because of its perceived objectivity over a human ( Pethig and Kroenung, 2023 ), (2) algorithms are perceived as less discriminatory than humans, which increases people’s comfort toward their usage ( Jago and Laurin, 2021 ), and (3) applicants with prior discrimination experiences deem algorithm-based decisions more positively than those without such experiences ( Koch-Bayram et al, 2023 ).…”
Section: Algorithms As a Solution Against Biasmentioning
confidence: 99%